PERLINDUNGAN HUKUM BAGI PIHAK YANG DIRUGIKAN ATAS PENYALAHGUNAAN KEADAAN DALAM PEMBUATAN SURAT KESEPAKATAN BERSAMA PEMBAYARAN UTANG PIUTANG - Sesar Gummara; Wira Franciska; Putra Hutomo (SINERGI : Jurnal Riset Ilmiah, 2026)
The abuse of circumstances (misbruik van omstandigheden) is an act that exploits an unbalanced position between parties in an agreement to obtain economic benefits, which can force one party to enter into an agreement with disproportionate performance. This phenomenon often occurs in the creation of joint agreement deeds for debt payments, as seen in several court rulings, where the economically or psychologically stronger party exploits the weaknesses of the other party. This contradicts the principles of freedom of contract and consensualism in the Indonesian Civil Code (KUH Perdata), thus requiring legal protection for the aggrieved party. This research aims to examine and analyze the legal protection for parties harmed by the abuse of circumstances in the creation of joint agreement deeds for debt payments, as well as to analyze the legal consequences arising from such abuse. This research employs a normative juridical legal research method with approaches encompassing legislation, case studies, analysis, and concepts. Primary legal sources include the Civil Code (KUH Perdata), the Notary Public Law, and court decisions, while secondary and tertiary sources are derived from library materials such as books, journals, and legal dictionaries. Data collection techniques are conducted through literature studies, and data analysis utilizes descriptive analytic qualitative methods to describe and construct an understanding of the related legal issues. The research results show that the legal consequences of abuse of circumstances are that the agreement can be annulled or void by law, so the agreement is considered never to have existed and can be restored to its original condition, provided that the aggrieved party submits an application for annulment. Legal protection for the aggrieved party can be obtained through the mechanism of applying for annulment of the agreement based on the doctrine of abuse of circumstances as a defect of will, which allows the judge to annul the agreement if it is proven that there is exploitation of a weak position. This research provides theoretical and practical contributions to the development of legal science as well as considerations in making fair agreements